Inhibition of UCH-L1 in oligodendroglial cells results in microtubule stabilization and prevents α-synuclein aggregate formation by activating the autophagic pathway: implications for multiple system atrophy - Pukaß, Katharina; Richter-Landsberg, Christiane (Frontiers in Cellular Neuroscience, 2015)
α-Synuclein (α-syn) positive glial cytoplasmic inclusions (GCI) originating in oligodendrocytes are a characteristic hallmark in multiple system atrophy. Their occurrence may be linked to a failure of the ubiquitin proteasome system (UPS) or the autophagic pathway. For proteasomal degradation, proteins need to be covalently modified by ubiquitin, and deubiquitinated by deubiquitinating enzymes before proteolytic degradation is performed. The deubiquitinating enzyme UCH-L1 is a component of the UPS, it is abundantly expressed in neuronal brain cells and has been connected to Parkinson`s disease. It interacts with α-syn and tubulin. The present study was undertaken to investigate whether UCH-L1 is a constituent of oligodendrocytes, the myelin forming cells of the CNS, and is associated with GCIs in MSA. Furthermore, LDN-57444 (LDN), a specific UCH-L1 inhibitor, was used to analyze its effects on cell morphology, microtubule organization and the proteolytic degradation system. Towards this an oligodendroglial cell line (OLN cells), stably transfected with α-syn or with α-syn and GFP-LC3, to monitor the autophagic flux, was used. The data show that UCHL-1 is expressed in oligodendrocytes derived from the brains of newborn rats and colocalizes with α-syn in GCIs of MSA brain sections. LDN treatment had a direct impact on the microtubule network by affecting tubulin posttranslational modifications, i.e. acetylation and tyrosination. An increase in α-tubulin detyrosination was observed and detyrosinated microtubules were abundantly recruited to the cellular extensions. Furthermore, small α-syn aggregates, which are constitutively expressed in OLN cells overexpressing α-syn, were abolished, and LDN caused the upregulation of the autophagic pathway. Our data add to the knowledge that the UPS and the autophagy-lysosomal pathway are tightly balanced, and that UCH-L1 and its regulation may play a role in neurodegenerative diseases with oligodendroglia pathology.